Breast Cancer Risk Analysis by the Use of Hormonal Contraceptives and Age of Menarche - Gusti Ayu Triara Dewi; Lucia Yovita Hendrati (Universitas Airlangga, 2015)
The incidence of breast cancer continues to increase and is a serious health problem in the world, including in Indonesia. High estrogen exposure is one factor that can increase the risk of breast cancer in women. This study was conducted to determine the relationship of estrogen exposure through the use of hormonal contraceptives and the age of menarche with the incidence of breast cancer in women. This type of research is observational analytic and uses a case-control research design. The case population in this study was all female patients who were diagnosed with breast cancer by a doctor at Regional Public Hospital of Dr. Soetomo (RSUD Dr. Soetomo) in 2013. The control population in this study was all female patients who performed breast examinations at RSUD Dr. Soetomo in 2013 but was not diagnosed with breast cancer by a doctor. The number of respondents in this study was 90 respondents drawn from the population using the simple random sampling method. The variables studied were the use of hormonal contraception and the age of menarche. The results of the analysis using multiple logistic regression tests (α = 5%) showed that the use of hormonal contraceptives (p = 0.028; OR = 3.266) and the age of menarche (p = 0.031; OR = 3.492) had a significant relationship to the incidence of breast cancer in women in RSUD Dr. Soetomo in 2013. It is hoped that the community can be more careful in determining the duration of using hormonal contraception and avoiding lifestyles that can accelerate the occurrence of menarche.